A semi-synthetic regulon enables rapid growth of yeast on xylose - Venkatesh Endalur Gopinarayanan (Nature Portfolio, 2018)
Efficient assimilation of nutrients is essential for the production of value-added products in microbial fermentation. Here the authors design a semi-synthetic xylose regulon to improve growth characteristics of Saccharomyces cerevisiae on this non-native sugar.